2004
DOI: 10.2169/internalmedicine.43.69
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Hyalinizing Granuloma with Laryngeal and Subcutaneous Involvement: Report of a Case Successfully Treated with Glucocorticoids

Abstract: We report a case of pulmonary hyalinizing granuloma (PHG) with laryngeal and subcutaneous involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 8 publications
0
18
0
1
Order By: Relevance
“…1,5) There is no specific treatment for PHG, but cases treated successfully with glucocorticoid have been reported. 8) In this case, ten months have passed since surgery, and there is no sign of recurrence. Because the etiology and clinical course of PHG are unclear, further accumulation of such cases will be needed to investigate its etiology and treatment.…”
Section: Discussionmentioning
confidence: 69%
“…1,5) There is no specific treatment for PHG, but cases treated successfully with glucocorticoid have been reported. 8) In this case, ten months have passed since surgery, and there is no sign of recurrence. Because the etiology and clinical course of PHG are unclear, further accumulation of such cases will be needed to investigate its etiology and treatment.…”
Section: Discussionmentioning
confidence: 69%
“…(2,8) There have been reports of extrapulmonary manifestations affecting the kidneys, larynx, and skin. (9,10) In the case reported here, the patient presented with skin involvement, characterized by a subcutaneous nodule. The nodule was investigated through biopsy and diagnosed as osteoma cutis, examination of the excised lobe revealed a welldelineated, firm, grayish-white mass, presenting calcified areas and measuring 10.0 × 4.0 × 3.5 cm (Figure 2).…”
Section: Case Reportmentioning
confidence: 83%
“…Regarding the therapeutic approach, no specific drug is recommended; however, there have been reports of patients who responded well to corticosteroid therapy at initial doses of 40-60 mg/day. (10) …”
Section: Discussionmentioning
confidence: 99%
“…Engleman et al (1977) reported sclerosing mediastinitis developed in 4 of the 20 patients. Shinohara et al (2004) reported that although there is no established treatment for PHG, the laryngeal tumor diminished and all other lesions disappeared with glucocorticoid treatment. During 1 months of follow-up in our patient, the posterior uveitis mildly resolved with glucocorticoid treatment.…”
Section: Discussionmentioning
confidence: 99%